Carbon nanotube-based composite ionic material, preparation method thereof and vertical temperature difference power generation device
Patent Information
- Application Number
- CN202611127385.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-09
AI Technical Summary
[0003]然而,现有技术中基于聚丙烯酸凝胶的离子导体材料仍存在明显不足:其一,传统有机离子凝胶普遍缺乏连续高效的电子传导网络,电子导电性较差,导致器件内阻高、热电输出效率低;其二,凝胶基体的力学强度与柔韧性难以兼顾,脆性大或易变形,难以满足柔性器件对结构稳定性的要求;其三,氧化还原活性离子(如Fe(CN)63-/4-)多通过物理掺杂方式引入,与聚合物基体界面结合力弱,在长期使用过程中易发生溶出流失,造成电化学性能快速衰减,循环稳定性差;其四,常规水凝胶在低温环境下易冻结失水,导致离子传导中断与力学性能劣化,严重限制了材料的使用温度范围与工况适应性
本发明提出的基于碳纳米管的复合离子材料,以碳纳米管为三维导电骨架,以聚丙烯酸凝胶为柔性基体,通过后浸渍法引入Fe(CN)63-/4-氧化还原电对,构筑电子-离子双连续传导网络。碳纳米管贯穿凝胶基体形成连续稳定的三维电子传导通路,显著降低体系电子传输阻抗;Fe(CN)63-/4-氧化还原电对依托凝胶多孔网络实现快速可逆的氧化还原反应与高效离子迁移,二者协同使复合材料同时具备优异的电子导电能力与离子传导特性,表现出优良的热电响应性能。同时,均匀分散的碳纳米管作为纳米增强相与物理交联节点,有效提升凝胶基体的拉伸强度、压缩强度与整体结构稳定性;丙三醇作为增塑剂插入聚丙烯酸分子链间,在保障力学强度的前提下改善链段运动能力,赋予材料良好柔韧性,并通过多羟基结构束缚自由水、降低体系冰点,使材料兼具优异的保水性与低温抗冻性能。
Smart Images

Figure CN122878697A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of composite material technology, specifically relating to a composite ionic material based on carbon nanotubes, its preparation method, and a vertical thermoelectric power generation device. Background Technology
[0002] With the rapid development of flexible electronics, wearable devices, and low-grade heat recovery technologies, flexible ion conductor materials with both electronic and ion conduction functions have become a research hotspot in the fields of energy conversion and sensing. Among them, polyacrylic acid (PAA)-based hydrogels are widely used as matrix materials for flexible ion conductors due to their advantages such as simple preparation process, low cost, good biocompatibility, and ease of functionalization modification. By introducing one-dimensional conductive fillers such as carbon nanotubes, electron transport channels can be constructed in the gel network; simultaneously, Fe(CN)6 is introduced... 3- / 4- Iso-redox couples can endow materials with ion conduction and thermoelectric conversion activity, enabling composite materials to show broad application prospects in fields such as flexible thermoelectric power generation, electrochemical sensing and energy storage.
[0003] However, existing ion conductor materials based on polyacrylic acid gels still have significant shortcomings: First, traditional organic ion gels generally lack a continuous and efficient electronic conduction network, resulting in poor electronic conductivity, high internal resistance, and low thermoelectric output efficiency. Second, it is difficult to balance the mechanical strength and flexibility of the gel matrix, leading to brittleness or easy deformation, which makes it difficult to meet the structural stability requirements of flexible devices. Third, redox-active ions (such as Fe(CN)6) 3- / 4- The main types of hydrogels are introduced through physical doping, resulting in weak interfacial bonding with the polymer matrix. They are prone to dissolution and loss during long-term use, leading to rapid degradation of electrochemical performance and poor cycle stability. Fourth, conventional hydrogels are prone to freezing and water loss at low temperatures, which interrupts ion conduction and deteriorates mechanical properties, severely limiting the material's operating temperature range and adaptability to various working conditions.
[0004] Therefore, there is an urgent need to develop a composite ionic material that combines high electron / ion dual continuous conduction characteristics, excellent mechanical strength and flexibility, good water retention and antifreeze properties, and long-term cycling stability, in order to solve the technical bottlenecks of existing flexible ionic conductors in terms of conductivity, mechanical properties, environmental tolerance, and service life, and meet the practical application requirements of flexible thermoelectric conversion devices for high efficiency, stability, and long life. Summary of the Invention
[0005] This invention aims to solve the technical problems existing in the prior art, and provides a composite ionic material based on carbon nanotubes, its preparation method, and a vertical thermoelectric power generation device. The material uses carbon nanotubes as a three-dimensional conductive framework and polyacrylic acid gel as a flexible matrix, and introduces Fe(CN)6 through a post-impregnation method.3- / 4- Redox couples construct a bicontinuous electron-ion conduction network; carbon nanotubes form a three-dimensional electron conduction pathway to reduce electron transport impedance, Fe(CN)6 3- / 4- The redox couple provides rapid and reversible redox activity and ion conductivity, which synergistically endow the material with excellent thermoelectric response properties. Meanwhile, carbon nanotubes, acting as nano-reinforcing phases and physical cross-linking nodes, enhance the tensile strength, compressive strength, and structural stability of the gel. Glycerol, as a plasticizer, imparts good flexibility and water retention, and significantly lowers the freezing point of the system to improve low-temperature antifreeze performance. Furthermore, the carboxyl groups and carboxylate groups (–COO) in the polyacrylic acid chain... - ) and Fe(CN)6 3- / 4- The cyano groups form hydrogen bonds and electrostatic complexes, which, combined with the physical confinement effect of the dense three-dimensional gel network, effectively inhibit the dissolution and loss of redox active ions, significantly improving the structural integrity and electrochemical stability of the composite material during long-term cyclic use.
[0006] To achieve the above objectives, the present invention employs the following technical solution: The first aspect of this invention provides a method for preparing a composite ionic material based on carbon nanotubes, comprising the following steps: S1. Carbon nanotubes and acrylic acid are ultrasonically dispersed in ethanol to obtain dispersion A; S2. Mix deionized water and glycerol to prepare mixed solvent B; S3. Acrylic acid and mixed solvent B are thoroughly stirred to obtain solution C. Then, dispersion A obtained in step S1 is added to solution C and stirred to obtain dispersion D. Then, ammonium persulfate is added to dispersion D and stirred under low temperature conditions to obtain dispersion E. S4. Dispersion E is dropped into a polytetrafluoroethylene mold and heat-treated to obtain a carbon nanotube composite gel organic matrix. S5. Immerse the carbon nanotube composite gel organic matrix obtained in step S4 in Fe(CN)6. 3- / 4- In solution, a composite ionic material based on carbon nanotubes was obtained.
[0007] Specifically, in step S1, carbon nanotubes, acrylic acid, and ethanol are added to ethanol at a mass ratio of 1:10 to 1:100. The concentration of the carbon nanotube dispersion is 10 mg / mL, the concentration of the acrylic acid is 50 mg / mL, and the sonication time is 2-8 h.
[0008] Specifically, in step S2, the volume ratio of glycerol to deionized water is 1:1-10, the stirring speed is 200-800 rpm, and the stirring time is 10-60 min.
[0009] Specifically, in step S3, the volume ratio of acrylic acid to mixed solvent B is 1:1-3, the stirring speed is 200-800 rpm, and the stirring time is 10-60 min.
[0010] Specifically, in step S3, the volume ratio of solution C to dispersion A is 6:1-4, the stirring speed is 200-800 rpm, and the stirring time is 10-60 min.
[0011] Specifically, in step S3, the amount of ammonium persulfate added is 1% of the mass of acrylic acid, the low temperature condition is 5℃, the stirring speed is 200-800 rpm, and the stirring time is 10-120 min.
[0012] Specifically, in step S4, the heat treatment temperature of dispersion D is 70℃, and the time is 12-48 h.
[0013] Specifically, in step S5, Fe(CN)6 3- / 4- The concentration of the solution is 0.01-0.4 mol / L, and the soaking time is 2-48 h.
[0014] A second aspect of the present invention also provides a carbon nanotube-based composite ionic material prepared by the above-described preparation method.
[0015] A third aspect of the present invention provides a vertical thermoelectric power generation device, comprising a plurality of carbon nanotube-based composite ionic materials, carbon paper, copper foil, and polyimide film; Each composite ionic material is covered with carbon paper on both its top and bottom ends. Adjacent composite ionic materials are connected in series via copper foil. The polyimide film encapsulates the multiple composite ionic materials covered with carbon paper and connected in series.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The composite ionic material based on carbon nanotubes proposed in this invention uses carbon nanotubes as a three-dimensional conductive framework and polyacrylic acid gel as a flexible matrix, and introduces Fe(CN)6 through a post-impregnation method. 3- / 4- Redox couples construct a continuous electron-ion conduction network. Carbon nanotubes penetrate the gel matrix to form a continuous and stable three-dimensional electron conduction pathway, significantly reducing the system's electron transport impedance; Fe(CN)6 3- / 4-Redox couples, relying on the porous network of the gel, enable rapid and reversible redox reactions and efficient ion migration. The synergy of these two factors endows the composite material with both excellent electronic conductivity and ion conductivity, exhibiting superior thermoelectric response performance. Meanwhile, uniformly dispersed carbon nanotubes, acting as nano-reinforcing phases and physical cross-linking nodes, effectively enhance the tensile strength, compressive strength, and overall structural stability of the gel matrix. Glycerol, as a plasticizer, is inserted between the polyacrylic acid molecular chains, improving chain segment mobility while ensuring mechanical strength, thus imparting good flexibility to the material. Furthermore, the polyhydroxy structure binds free water and lowers the freezing point of the system, giving the material both excellent water retention and low-temperature antifreeze properties.
[0017] The composite ionic material based on carbon nanotubes proposed in this invention contains carboxyl groups (–COOH) and deprotonated carboxylate groups (–COO) on the polyacrylic acid molecular chain. - It can react with Fe(CN)6 3- / 4- The cyano groups form hydrogen bonds and electrostatic complexes, which, combined with the physical embedding and confinement effect of the dense three-dimensional gel network, fix redox active ions from both the interface and structural dimensions, effectively inhibiting the dissolution and loss of redox couples, and significantly improving the structural integrity and electrochemical stability of the composite material during long-term cyclic use. Attached Figure Description
[0018] Figure 1 The curves showing the relationship between open-circuit voltage and temperature difference of the composite ionic materials based on carbon nanotubes in Examples 1-4 of this invention; Figure 2 The bar chart shows the ionic thermoelectric potential values of the composite ionic materials based on carbon nanotubes in Examples 1-4 of this invention. Figure 3 A bar chart showing the ionic conductivity values of the carbon nanotube-based composite ionic materials in Examples 1-4 of this invention; Figure 4 This is a schematic diagram of the structure of a vertical thermoelectric power generation device provided by the present invention. Figure 5 The circuit voltage and output current of a vertical thermoelectric generator provided by the present invention under different loads at a temperature difference of 6 K. Figure 6 The output power of a vertical thermoelectric generator provided by the present invention under different loads at a temperature difference of 6 K; 1- Carbon nanotube-based composite ionic material; 2- Carbon paper; 3- Copper foil; 4- Polyimide film. Detailed Implementation
[0019] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used in the specification and claims are explained and defined in general below. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.
[0020] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.
[0021] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values (including integers and fractions) within those ranges.
[0022] In this article, unless otherwise specified, “contains,” “includes,” “containing,” “has,” or similar terms cover the meanings of “composed of” and “mainly composed of,” for example, “A contains a” covers the meanings of “A contains a and others” and “A contains only a.”
[0023] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.
[0024] This invention provides a method for preparing composite ionic materials based on carbon nanotubes, comprising the following steps: S1. Preparation of Dispersion A: Carbon nanotubes and acrylic acid were added to ethanol at a mass ratio of 1:1 to 10:100 and ultrasonically dispersed. The concentration of the carbon nanotube dispersion was 10 mg / mL and the concentration of the acrylic acid was 50 mg / mL. The ultrasonic time was 2-8 h.
[0025] S2, Preparation of mixed solvent B: Prepare mixed solvent B by mixing glycerol and deionized water at a volume ratio of 1:1-10, and stir at a speed of 200-800 rpm for 10-60 min.
[0026] S3, Preparation of Dispersion E: Acrylic acid and mixed solvent B are stirred thoroughly at a volume ratio of 1:1-3 to obtain solution C, with a stirring speed of 200-800 rpm and a stirring time of 10-60 min. Then, solution C and dispersion A obtained in step S1 are stirred thoroughly at a volume ratio of 6:1-4 to obtain dispersion D, with a stirring speed of 200-800 rpm and a stirring time of 10-60 min. Finally, ammonium persulfate (1% of the mass of acrylic acid) is added to dispersion D and stirred at 5°C at a stirring speed of 200-800 rpm for 10-120 min.
[0027] Preparation of S4 carbon nanotube composite gel organic matrix: Dispersion E was dropped into a polytetrafluoroethylene mold and heat-treated at 70°C for 12-48 h.
[0028] S5. Preparation of composite ionic materials based on carbon nanotubes: The carbon nanotube composite gel organic matrix obtained in step S4 was immersed in Fe(CN)6 solution with a concentration of 0.01-0.4 mol / L. 3- / 4- Soaking time in solution is 2-48 h.
[0029] The present invention also provides a carbon nanotube-based composite ionic material prepared by the method described above.
[0030] like Figure 4 As shown, the present invention also provides a vertical thermoelectric power generation device using a composite ionic material based on carbon nanotubes, the device comprising multiple composite ionic materials based on carbon nanotubes 1, carbon paper 2, copper foil 3, and polyimide film 4. Each of the carbon nanotube-based composite ionic materials 1 has carbon paper 2 covering both its upper and lower ends. Two adjacent carbon nanotube-based composite ionic materials 1 are connected in series by copper foil 3. The polyimide film 4 encapsulates the multiple carbon nanotube-based composite ionic materials 1 that are covered with carbon paper 2 and connected in series.
[0031] The specific method for assembling a vertical thermoelectric generator is as follows: the upper and lower ends of the composite ionic material 1 based on carbon nanotubes are covered with carbon paper 2, multiple composite ionic materials 1 based on carbon nanotubes are connected in series with copper foil 3, and finally encapsulated with polyimide film 4.
[0032] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.
[0033] The following examples use instruments and equipment conventional in the art. Experimental methods in the following examples, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. All raw materials used in the following examples are conventional commercially available products with specifications conventional in the art. In this specification and the following examples, unless otherwise specified, "%" refers to weight percentage, "parts" refers to parts by weight, and "ratio" refers to weight proportion.
[0034] Example 1: A method for preparing a composite ionic material based on carbon nanotubes includes the following steps: Step 1: Weigh 200 mg of carbon nanotubes, add 1 g of acrylic acid, then add 20 mL of ethanol, and sonicate for 4 h to obtain dispersion A. In dispersion A, the concentration of carbon nanotubes is 10 mg / mL, and the concentration of acrylic acid is 100 mg / mL. Step 2: Stir 0.5 mL of glycerol and 2.5 mL of deionized water at 500 rpm for 30 min to obtain mixed solvent B. Step 3: Add 3 mL of acrylic acid to the mixed solvent B obtained above, and stir at 500 rpm for 30 min to obtain solution C. Then add 1 mL of dispersion A obtained in Step 1, and stir at 500 rpm for 30 min to obtain solution D. Finally, add 30 mg of ammonium persulfate, and stir at 0-5℃ for 60 min at 500 rpm to obtain dispersion E. Step 4: Drop dispersion E into a polytetrafluoroethylene mold and heat-treat at 70℃ for 24 hours to polymerize. h, to obtain a carbon nanotube composite gel organic matrix; step 5, immerse the carbon nanotube composite gel organic matrix in 0.1 mol / L Fe(CN)6. 3- / 4- After 6 h in solution, a composite ionic material based on carbon nanotubes was obtained.
[0035] Example 2: A method for preparing a composite ionic material based on carbon nanotubes includes the following steps: Step 1: Weigh 200 mg of carbon nanotubes, add 1 g of acrylic acid, then add 20 mL of ethanol, and sonicate for 4 h to obtain dispersion A. In dispersion A, the concentration of carbon nanotubes is 10 mg / mL, and the concentration of acrylic acid is 100 mg / mL. Step 2: Stir 0.5 mL of glycerol and 2.5 mL of deionized water at 500 rpm for 30 min to obtain mixed solvent B. Step 3: Add 3 mL of acrylic acid to the mixed solvent B obtained above, and stir at 500 rpm for 30 min to obtain solution C. Then add 2 mL of dispersion A obtained in Step 1, and stir at 500 rpm for 30 min to obtain solution D. Finally, add 30 mg of ammonium persulfate, and stir at 0-5℃ for 60 min at 500 rpm to obtain dispersion E. Step 4: Drop dispersion E into a polytetrafluoroethylene mold and heat-treat at 70℃ for 24 hours to polymerize. h, to obtain a carbon nanotube composite gel organic matrix; step 5, immerse the carbon nanotube composite gel organic matrix in 0.1 mol / L Fe(CN)6. 3- / 4- After 6 h in solution, a composite ionic material based on carbon nanotubes was obtained.
[0036] Example 3: A method for preparing a composite ionic material based on carbon nanotubes includes the following steps: Step 1: Weigh 200 mg of carbon nanotubes, add 1 g of acrylic acid, then add 20 mL of ethanol, and sonicate for 4 h to obtain dispersion A. In dispersion A, the concentration of carbon nanotubes is 10 mg / mL, and the concentration of acrylic acid is 100 mg / mL. Step 2: Stir 0.5 mL of glycerol and 2.5 mL of deionized water at 500 rpm for 30 min to obtain mixed solvent B. Step 3: Add 3 mL of acrylic acid to the mixed solvent B obtained above, and stir at 500 rpm for 30 min to obtain solution C. Then add 3 mL of dispersion A obtained in Step 1, and stir at 500 rpm for 30 min to obtain solution D. Finally, add 30 mg of ammonium persulfate, and stir at 0-5℃ for 60 min at 500 rpm to obtain dispersion E. Step 4: Drop dispersion E into a polytetrafluoroethylene mold and heat-treat at 70℃ for 24 hours to polymerize. h, to obtain a carbon nanotube composite gel organic matrix; step 5, immerse the carbon nanotube composite gel organic matrix in 0.1 mol / L Fe(CN)6. 3- / 4- After 6 h in solution, a composite ionic material based on carbon nanotubes was obtained.
[0037] Comparative Example 1: A method for preparing a composite ionic material based on carbon nanotubes includes the following steps: Step 1: Weigh 200 mg of carbon nanotubes, add 1 g of acrylic acid, then add 20 mL of ethanol, and sonicate for 4 h to obtain dispersion A. In dispersion A, the concentration of carbon nanotubes is 10 mg / mL, and the concentration of acrylic acid is 100 mg / mL. Step 2: Stir 0.5 mL of glycerol and 2.5 mL of deionized water at 500 rpm for 30 min to obtain mixed solvent B. Step 3: Add 3 mL of acrylic acid to the mixed solvent B obtained above, and stir at 500 rpm for 30 min to obtain solution C. Then add 3 mL of dispersion A obtained in Step 1, and stir at 500 rpm for 30 min to obtain solution D. Finally, add 30 mg of ammonium persulfate, and stir at 0-5℃ for 60 min at 500 rpm to obtain dispersion E. Step 4: Drop dispersion E into a polytetrafluoroethylene mold and heat-treat at 70℃ for 24 hours to polymerize. h, to obtain a carbon nanotube composite gel organic matrix; step 5, immerse the carbon nanotube composite gel organic matrix in 0.1 mol / L Fe(CN)6. 3- / 4- After 12 h in solution, a composite ionic material based on carbon nanotubes was obtained.
[0038] A method for assembling a vertical thermoelectric generator includes the following steps: The top and bottom ends of the carbon nanotube-based composite ionic material 1 prepared in Example 1 are covered with carbon paper 2, three carbon nanotube-based composite ionic materials 1 are connected in series with copper foil 3, and finally encapsulated with a polyimide film 4. A schematic diagram of the structure of the vertical thermoelectric generator of the present invention is shown below. Figure 4 As shown. One end of the device is at the hot end, and the other end is at the cold end. By controlling the temperatures of the hot and cold ends, different temperature differences can be achieved.
[0039] Figure 1 The composite ionic materials prepared in the examples and comparative examples show the change in voltage difference of the materials with temperature changes at the same temperature difference. It can be seen that the voltage difference in Example 2 shows a linear increasing trend with increasing temperature difference. Figure 2 The graph shows the test results of the ionic thermoelectric potential of the composite ionic materials prepared in the examples and comparative examples. It can be seen that Example 2 has a higher thermoelectric potential. Figure 3 The test results of the ionic conductivity of the composite ionic materials prepared for the examples and comparative examples show that the conductivity of Example 2 is much higher than that of the comparative example.
[0040] The composite ionic material prepared in Example 2 was assembled into a vertical thermoelectric generator and connected to a loaded circuit at a temperature difference of 6 K. By adjusting the resistance of the load, the load circuit voltage and output current of the device were tested (e.g., ...). Figure 5 As shown in the figure, its output power can then be calculated. From... Figure 6 It can be seen that when the load resistance is -9300 Ω, the maximum output power is 1.76 μW, indicating that Example 2 has higher thermoelectric performance.
[0041] This invention provides a carbon nanotube-based composite ionic material, its preparation method, and a vertical thermoelectric generator. The material uses carbon nanotubes as a conductive framework and polyacrylic acid gel as a matrix, with Fe(CN)6 subsequently impregnated into it. 3- / 4- Redox couples construct an electron-ion bicontinuous conduction network; carbon nanotubes reduce electron transport impedance, Fe(CN)6 3- / 4- It provides ion conduction and redox activity, synergistically enhancing thermoelectric response. Carbon nanotubes strengthen the gel's mechanical and structural stability, while glycerol imparts flexibility, water retention, and antifreeze properties; the carboxyl / carboxylate groups in the polyacrylic acid chain and Fe(CN)6... 3- / 4- It forms hydrogen bonds and electrostatic complexes, and combines the physical confinement of gel to fix active ions, inhibiting dissolution and loss, and improving long-term cycling stability.
[0042] The above content is only for illustrating the technical concept of the present invention and should not be construed as limiting the scope of protection of the present invention. Any modifications made to the technical solution based on the technical concept proposed in this invention shall fall within the scope of protection of this invention.
Claims
1. A method for preparing a composite ionic material based on carbon nanotubes, characterized in that, Includes the following steps: S1. Carbon nanotubes and acrylic acid are ultrasonically dispersed in ethanol to obtain dispersion A; S2. Mix deionized water and glycerol to prepare mixed solvent B; S3. Acrylic acid and mixed solvent B are thoroughly stirred to obtain solution C. Then, dispersion A is added to solution C and stirred to obtain dispersion D. Then, ammonium persulfate is added to dispersion D and stirred under low temperature conditions to obtain dispersion E. S4. Dispersion E is dropped into a polytetrafluoroethylene mold and heat-treated to obtain a carbon nanotube composite gel organic matrix. S5. The carbon nanotube composite gel organic matrix was immersed in Fe(CN)6. 3- / 4- In solution, a composite ionic material based on carbon nanotubes was obtained.
2. The method for preparing a composite ionic material based on carbon nanotubes according to claim 1, characterized in that, In S1, the mass ratio of carbon nanotubes, acrylic acid, and ethanol is 1:1 to 10:100, the concentration of dispersion A is 10 mg / mL, the concentration of acrylic acid is 50 mg / mL, and the sonication time is 2-8 h.
3. The method for preparing a composite ionic material based on carbon nanotubes according to claim 1, characterized in that, In S2, the volume ratio of glycerol to deionized water is 1:1-10.
4. The method for preparing a composite ionic material based on carbon nanotubes according to claim 1, characterized in that, In S3, the volume ratio of acrylic acid to mixed solvent B is 1:1-3.
5. The method for preparing a composite ionic material based on carbon nanotubes according to claim 1, characterized in that, In S3, the volume ratio of solution C to dispersion A is 6:1-4.
6. The method for preparing a composite ionic material based on carbon nanotubes according to claim 1, characterized in that, In S3, the amount of ammonium persulfate added is 1% of the mass of acrylic acid, and the temperature of the low-temperature condition is 5°C.
7. The method for preparing a composite ionic material based on carbon nanotubes according to claim 1, characterized in that, In S4, the heat treatment temperature of the dispersion D is 70°C, and the time is 12-48 h.
8. The method for preparing a composite ionic material based on carbon nanotubes according to claim 1, characterized in that, In S5, the Fe(CN)6 3- / 4- The concentration of the solution was 0.01-0.4 mol / L, and the soaking time was 2-48 h.
9. A composite ionic material based on carbon nanotubes, characterized in that, The composite ionic material based on carbon nanotubes was prepared using any one of claims 1 to 8.
10. A vertical thermoelectric generator, characterized in that, Includes the composite ionic materials based on carbon nanotubes, carbon paper, copper foil, and polyimide film as described in claim 9; Each composite ionic material is covered with carbon paper on both its top and bottom ends. Adjacent composite ionic materials are connected in series via copper foil. The polyimide film encapsulates the multiple composite ionic materials covered with carbon paper and connected in series.